Pengaruh tiga jenis pupuk kotoran ternak (sapi, ayam, kambing) terhadap pertumbuhan dan produksi rumput Brachiaria humidicola - Budya Satata; Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
The aims of this research were to know the effect of three kind manures (cow, chicken, and goat) and to know the kind of manure that giving the best result to the growth and production of Brachiaria humidicola. This research was conducted in the experiment station farm of Animal Science Faculty, Palangka Raya Christian University. This research was designed by using completely random design (CRD) with single experiment factor. The result showed that the applications of three kind manure giving the effect to the number of tillers, the crop height, and the production of Brachiaria humidicola. Chicken manure was gived the best result of the tiller number and the production of Brachiaria humidicola